Signalling pathways involved in IL-8 mediated odontogenic differentiation of shed cultured on human amniotic membrane with BMP-2 - Osman, Zul Faizuddin (2021)
Current knowledge about the treatment modalities using amniotic membrane (AM) scaffold for dental regeneration is still limited. It has been previously shown that bone morphogenetic protein-2 (BMP-2) growth factor assisted stem cells from human exfoliated deciduous teeth (SHED) differentiation into odontoblast-like cells via activation of interleukin-8 (IL-8) cytokine. Nevertheless, the fundamental biology of IL-8 mediation in the process is yet to be understood. This study aims at finding the roles and mechanisms of IL-8 immunomodulatory pathway during odontoblast differentiation of SHED. In this study, SHED was cultured on AM scaffold with BMP-2 treatment. Flow cytometry analysis, multiplex polymerase chain reaction (PCR), and Western blot were conducted to determine the expression of stem cell markers, the expression of inflammatory cytokines genes, the protein expression of odontoblast markers, and molecules involved in the IL-8 immunomodulatory pathways. Finally, the ultrastructure of SHED and odontoblastlike cells were also investigated via scanning electron microscopy (SEM) imaging. The results presented in this thesis showed the potential of SHED to differentiate into odontoblast-like cells on AM scaffold. SHED was characterised, and exhibited expression profiles of various stem cell markers for the presence of mesenchymal stem cell (MSC) markers (cluster of differentiation) CD44, CD73, CD90, CD105 and the absence of hematopoietic markers CD34 and CD45 using flow cytometry analysis. The results also indicated that SHED revealed strong expression of MSC surface markers CD90, CD44 and CD73 with 100% expression while CD105 has 84.1% expression. Under stimulation with BMP-2, it was demonstrated that proinflammatory cytokines namely IL-8, IL-6, IL-1β, TGF-β and TNF-α were expressed. Successful differentiation of SHED into odontoblast-like cells was demonstrated by the expression of odontoblast markers such as dentin sialophosphoprotein (DSPP), dentin matrix protein 1 (DMP1), alkaline phosphatase (ALP) and osteopontin (OPN). Exogenous IL-8 showed to enhance the expression of odontogenic markers of DSPP, DMP1 and ALP. During the differentiation of SHED, high expression of IL-8 protein stimulated the cascades of signalling pathway of PI3K/Akt/NF-κB. This pathway is known to be responsible for regulating the biological process of cell survival, proliferation and differentiation. Visualisation of SHED ultrastructure further confirmed the differentiation process of SHED into odontoblast-like cells. Emerging of phenotypic characteristics of odontoblast-like cell with a columnar cell body and several processes as well as strong cell induced mineralisation on the cell body suggesting morphology of mature odontoblast. In conclusion, this study confirmed for the first time that complete differentiation process of SHED into odontoblast-like cells occur with BMP-2 stimulation within 14 days via IL-8 signalling pathways mediation.